2009 IEEE Pulsed Power Conference 2009
DOI: 10.1109/ppc.2009.5386317
|View full text |Cite
|
Sign up to set email alerts
|

On the interaction of non-thermal atmospheric pressure plasma with tissues

Abstract: Non-thermal atmospheric pressure plasma is now being widely developed for various clinical applications such as skin sterilization, blood coagulation, cancer treatment, angiogenesis and wound healing among others. However, understanding of mechanism of interaction between non-thermal plasma and mammalian cells is lacking. Here we investigated the possibility that the dose of non-thermal plasma can be tuned to achieve various results depending on the clinical applications ranging from enhanced cell proliferatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…24,28 To test the role of these ROS in non-thermal plasma-induced apoptosis, we pre-incubated melanoma cells for 1 h in 2.25 mM NAC, an intracellular scavenger of ROS, followed by treatment at a dose of 5 and 15 J/cm 2 . Apoptotic activity was assayed 24 h post-plasma treatment using Annexin-v/PI staining.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…24,28 To test the role of these ROS in non-thermal plasma-induced apoptosis, we pre-incubated melanoma cells for 1 h in 2.25 mM NAC, an intracellular scavenger of ROS, followed by treatment at a dose of 5 and 15 J/cm 2 . Apoptotic activity was assayed 24 h post-plasma treatment using Annexin-v/PI staining.…”
Section: Resultsmentioning
confidence: 99%
“…Both charged and neutral particles can lead to additional ROS production in the treated fluid. 24,28 Direct effects of non-thermal plasma treatment could include local heating caused by plasma streamers or UV radiation. Non-thermal atmospheric pressure DBD plasma is able to produce a large concentration of ROS in the extracellular media during treatment.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that proliferation of endothelial cells can be increased significantly through treatment by NTGP in air. Viable endothelial cell (PAEC) number was enhanced by a low dose floating electrode, dielectric barrier discharge (FE‐DBD) plasma treatment 105–107. These cells showed greater viable cell number than controls for up to 30 s of plasma treatment.…”
Section: How Can Ntgps Address These Unmet Needs?mentioning
confidence: 99%